VD_FINDINFO HC / 2016 / 172 vom 6. Januar 2016 - VD Tribunal cantonal (2016)
VENTE D'IMMEUBLE, DÉFAUT DE LA CHOSE, GARANTIE EN RAISON DES DÉFAUTS DE LA CHOSE | 197 CO, 219 CO, 368 CO, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH)